First Line of Defense: Innate Cell-Mediated Control of Pulmonary Aspergillosis - Espinosa, Vanessa; Rivera, Amariliz (Frontiers in Microbiology, 2016)
Mycotic infections and their effect on the human condition have been widely overlooked and poorly surveilled by many health organizations even though mortality rates have increased in recent years. The increased usage of immunosuppressive and myeloablative therapies for the treatment of malignant as well as non-malignant diseases has contributed significantly to the increased incidence of fungal infections. Invasive fungal infections have been found to be responsible for at least 1.5 million deaths worldwide. About 90% of these deaths can be attributed to Cryptococcus, Candida, Aspergillus, and Pneumocystis. A better understanding of how the host immune system contains fungal infection is likely to facilitate the development of much needed novel antifungal therapies. Innate cells are responsible for the rapid recognition and containment of fungal infections and have been found to play essential roles in defense against multiple fungal pathogens. In this review we summarize our current understanding of host-fungi interactions with a focus on mechanisms of innate cell-mediated recognition and control of pulmonary aspergillosis.